math

posted by .

also a problem that i cant figure out is how to do inverses of logs

f(x)= 2log(base2)X

  • math -

    f(x) = y
    y = 2log(base2)x
    =log(base2)x^2
    therefore
    2^y=x^2
    so x = sqrt(2^y)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    Could you show me step by step how to find the inverse of this problem: log with base of 2 (x+1) Thanks! It is not clear what the problem is. You are given a function of x. Let's calli it y. Are you trying to come up with an equation …
  2. LOGARITHMS

    HI THE QUESTION STATES THAT ONE SHOULD CALCULATE THE LOGS WITHOUT THE USE OF A CALCULATOR...OKAY MY PROBLEM IS THIS... 2 3 2log 8 + 2log 8 what should i do?
  3. Algebra 2

    How would I solve the equation: log(base2)4 - log(base2)(x+3) = log(base2)8 ?
  4. Algebra 2

    solve the equation: log(base2)^(x-3)log(base2)^5 = 2log(base2)^10 I don't know how to solve it, can someone help me?
  5. Math

    Logs are stacked up in apile as shown in the figure. The top row has 15 logs and the bottom row has 21 logs. How many logs are in the stack?
  6. Calculus

    I have trouble finding the second derivative, my answer is a little off from the answer key. f(x)=(log(base2)x)^5 f'(x)=[5(log(base2)x)^4]/xln2 f"(x)=[20(log(base2)x)³(xln2)-(ln2+(x/2))(5(log(base2)x)^4)]/[x²(ln2)²] for the f"(x), …
  7. Calculus

    Find the second derivative of the following function: y=log(base2)x/x² y'=[(x/ln2)-2xlog(base2)x]/x^4 the derivative of x/ln2 is (ln2)^-1?
  8. Precalculus-Verify

    log(base2)x-log(base2)6= log(base2)5+ 2log(base2)3 log(x/6)=3log15 (x/6)=15^3 6*(x/6)=15^3*6 x=15^3*6 =20,250 Answer is 270.... What did I do wrong...
  9. Computer Organization

    Help me solve this question by using 1's complement (i) 110(Base2) - 010(Base2) (ii) 1010(Base2) - 1000(Base2) Help me solve this question convert The Value -40 and 52 to 8-Bit digit in form of: (i) Sign and Magnitude (ii) 1's Complement …
  10. Algebra

    In the logarithmic expression . . . log(base 4) 8 , how does the base 4 become base 2?

More Similar Questions